Communicative Voice and Articulation - McCabe, Bernard P. (Holbrook Press, 1970)
Keywords: Voice culture; dept.cmd; faculty_collection

The Clinical Assessment of Language Comprehension - Miller, Jon F.; Paul, Rhea (P.H. Brookes Pub. Co., 1995)
Keywords: Diagnosis; Language acquisition; Language disorders in children; Testing; dept.cmd; faculty_collection

Handbook of Autism and Pervasive Developmental Disorders - Cohen, Donald J.; Donnellan, Anne M.; Paul, Rhea (Winston ; Wiley, 1987)
Keywords: Autism; Developmental disabilities; Autistic children; Services for; Services for; Developmentally disabled children; dept.cmd; faculty_collection

Contemporary Approaches in Stuttering Therapy - Peins, Maryann (Little, Brown, 1984)
Keywords: Stuttering; Treatment; Speech therapy; Treatment; Stuttering in children; dept.cmd; faculty_collection

Effects of interrupted normal speech flow on post-interruption speech rates - Sansone, F.E. (IRCS Medical Science: Nervous System, 1978)
Keywords: central nervous system; dept.cmd; human cell; larynx; normal human; speech; ⛔ No DOI found

Frequency and duration effects on perceptions of rise-time rate - Sansone Jr., F.E. (IRCS Medical Science, 1983)
The ability to accurately perceive the acoustic correlate of glottal attack, phonatory onset rise-time rate, can be diagnostically critical for speech pathologists conducting voice function examinations. Signal onset duration may serve as a cue in these perceptions because an inverse relationship exists between onset duration and rise-time rate. Other acoustic information such as frequency, present during voice initiation, might also affect phonatory onset rise-time perceptions. This study was designed to determine if listeners can detect duration related rise-time rate differences in the presence of variable frequency. Listeners accurately detected rise-time rates associated with onset duration differences independent of the frequency variable. A significant duration effect was revealed with no frequency or variable interaction effects. All judgement means were significantly different from one another. It was determined that as stimulus onset duration decreased, onset rise-time rate was perceived to occur more rapidly.
Keywords: auditory discrimination; auditory system; dept.cmd; hearing; human; human experiment; normal human; phonation; speech; ⛔ No DOI found

Effects of electronic voice intensity monitoring on hard glottal attack - Sansone Jr., F.E. (IRCS Medical Science, 1982)
An electronic device capable of monitoring the rate at which voice intensity increases during voice onset provides an indicator of the abruptness of phonatory initiation. Two groups of 8 subjects were taught to reduce the abruptness of glottal attack. Group A used a seven step program employing the electronic monitor while Group B used the same seven step program but with a traditional approach to the reduction of abrupt glottal attack substituted for monitor use. Both groups used a self-instruct teaching paradigm. Subject recordings of pre and post program production of five voice onset moments were submitted to sonographic amplitude analysis and a time/intensity slope ratio was calculated for each. Further, the pre and post program recordings were judged for abruptness of glottal attack. Post program slope ratios and attack judgments were significantly different (p < 0.01) from pre program data for Group A only. These data suggest that electronic monitoring was effective in producing gradual phonatory initiation.
Keywords: central nervous system; dept.cmd; glottis spasm; human cell; larynx; normal human; phonation; voice; ⛔ No DOI found

The 1989 Mary E. Switzer lecture: marketing health care services for the new millennium. - Holley, S.C. (Journal of allied health, 1990)
Keywords: Allied Health Personnel; Human; Marketing of Health Services; United States; article; dept.cmd; economics; financial management; human; paramedical personnel; ⛔ No DOI found

Predicting outcomes of early expressive language delay - Paul, R.; Fountain, R. (Infant-Toddler Intervention, 1999)
A group of children was identified as 'late talkers' who were slow in expressive language development (SELD) on the basis of small expressive vocabulary size at 20-34 months of age. The subjects were followed yearly throughout the preschool and early school-age periods in order to track growth in language and related skills. When the subjects were in second grade, their expressive language skills, as indexed by the Developmental Sentence Score, were measured. This measure was used as the outcome variable in regression and discriminant function analyses. Predictor variables included those gathered when the subjects entered the study at age 2. They included measures of early expressive and receptive language by parent report, nonverbal cognitive performance, Bayley Mental Scale score (a combined verbal and nonverbal cognitive measure), phonological skill, motor skills, maladaptive behaviors, social skills, birth order, socioeconomic (SES) level, and gender. Only SES and early expressive language skills predicted expressive language outcome in second grade. Discriminant function analysis revealed these two factors were significant in predicting success (scores above the tenth percentile), along with a contribution of early gross motor skills. The implications of these findings for understanding early language delays are discussed.
Keywords: article; child; child development; clinical article; dept.cmd; developmental disorder; discriminant analysis; female; human; language development; language disability; male; outcomes research; prediction; ⛔ No DOI found

Facilitating transitions in language development for children using AAC - Paul, R. (AAC: Augmentative and Alternative Communication, 1997)
Several major transitions in language use take place during the first 5 years of life. Each transition allows the child to move to a higher level of complexity of expression and to accomplish communicative goals more flexibly and precisely than was done at the previous level. At least three of these transitions appear to be modulated to some degree by speech. In the first transition, prellnguistic to early linguistic communication, babbling provides the infant with a prelinguistic form of vocal behavior that is in many ways analogous to language. A second transition takes place in the movement from single words to multiword combinations. In the process of this transition, word order becomes a means by which children convey semantic role information, and transitional forms such as successive one-word utterances help to facilitate the child's leap from single-word speech to multiword sentences. A third transition involves the development of phonological awareness, an important basis for the acquisition of literacy, which builds on the foundation laid by the phonological system for articulation. In each of these transitions, speech appears important for mediating the move to a higher language level. This paper considers the question of how these transitions can be facilitated in children who use augmentative and alternative communication rather than speech as a first expressive system, in order to provide as precise and flexible a communication modality as possible to children with severe speech impairments.
37 citations (Crossref) [2023-10-31]
Keywords: Augmentative and alternative communication (AAC); Biocommunications; Children with severe speech and physical impairments; Language acquisition; Linguistics; Pediatrics; Speech; dept.cmd

The effects of microphone spacing on auditory localization - Maxon, A.B.; Mazor, M. (International Journal of Audiology, 1977)
The localization ability of 10 normally hearing adults was determined under varying microphone separations and varying sound source azimuths. The stimuli (white noise bursts) were prerecorded, after being transduced through 'body' hearing aids and then played to the subjects over headphones. Results indicated that there was an improvement in localization ability for all azimuth conditions when the microphones were spaced wider than 12.7 cm apart (15.2-30.5 cm). The smaller the separations (5.5-12.7 cm), the poorer the localization. Localization was always poorer at 30° azimuth (the smallest used) than at any of the other azimuths (0° 30° 60° 90° right and left), regardless of microphone spacing. Implications are made about the relation of these findings to the use of binaural body aids on infants and young children. © 1977 Informa UK Ltd All rights reserved: reproduction in whole or part not permitted.
1 citations (Crossref) [2023-10-31]
Keywords: Acoustic Stimulation; Audiometry; Auditory Perception; Auditory localization; Binaural amplification; Female; Hearing Aids; Human; Male; Noise; Pediatric amplification; audiology; binaural hearing; child; dept.cmd; directional hearing; methodology; microphone

The initial psychotherapy interview: a content analysis of the verbal responses of novice and experienced therapists. - Cicchetti, Domenic V; Ornston, Patricia S (The Journal of Psychology, 1976)
This study tested and confirmed the clinical impressions that (a) the novice psychotherapist may focus so much upon the exact words and nonverbal behavior patterns of his client (the process of making “concrete” statements) that he may lose sight of the larger picture that his client may be revealing at any given moment during the interview; (b) the experienced psychotherapist, on the other hand, seems to be responding to the words of the patient at a level of abstraction that attempts to integrate and understand the messages that the patient is trying to convey about himself; and (c) this latter process is reflected in the making of relatively more “abstract” comments than is true of the novice. S s were 24 first-year psychiatric residents and 19 staff psychologists and psychiatrists at a veterans hospital and a medical school. The learning theory implications of these findings is discussed. © 1976 Taylor & Francis Group, LLC.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/042-998-362-275-980 tex.type: [object Object]
Keywords: Analysis of Variance; Clinical Competence; Comparative Study; Human; Interview; Psychological; Psychotherapy; Verbal Behavior; analysis of variance; article; comparative study; competence; dept.cmd; human; manpower; methodology; psychologic test; psychotherapy; verbal behavior

Perceived utility of a self-evaluation procedure by students in speech-language pathology - Mercaitis, Patricia A; Wener, Deena L (The Clinical Supervisor, 1988)
A 58-item Likert attitude scale was developed and administered to thirty Speech-Language Pathology graduate students in order to obtain their perceptions of a self-evaluation procedure used in a clinical training facility. Significant correlations were obtained between the clinicians’ perception of the overall usefulness of this self-evaluation procedure, and a majority (61%) of the items on the scale. Significant correlations were obtained for several pairs of demographic items. The implications of these results for the clinical supervision process are discussed, as well as the need for further research on this topic. © 1988 by The Haworth Press, Inc. All rights reserved.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/033-646-942-990-571 tex.type: [object Object]
Keywords: dept.cmd

Speech considerations in prosthodontic rehabilitation of the glossectomy patient - Mckinstry, Robert E; Aramany, Mohamed A; Beery, Quinter C; Sansone, Frank (Journal of Prosthetic Dentistry, 1985)
A knowledge of normal articulation is needed before the prosthodontist can assess the compensatory articulation used by glossectomy patients. The amount and portion of tongue resected is directly correlated with speech intelligibility. The loss of the tip of the tongue is more critical to intelligibility than a hemiglossectomy. Partial glossectomy speakers can often use the residual tongue stump to perform adaptive movements that approximate normal movements and should be treated as an articulation problem. The compensatory articulation used by the total glossectomy patient was reviewed. The prosthodontic management of patients with partial tongue resection often includes lowering the palatal vault, while the management of the total glossectomy patient usually requires a mandibular tongue prosthesis. These prostheses can be refined with the use of multiview videofluoroscopy, videotaping, and spectrographic analysis. © 1985.
12 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/058-110-990-398-611 tex.type: [object Object]
Keywords: Dentures; Glossectomy; Human; Mandible; Prostheses and Implants; Prosthesis Design; Speech Articulation Tests; Speech Disorders; Tongue; article; denture; dept.cmd; glossectomy; human; mandible; prostheses and orthoses; prosthesis; speech analysis; speech disorder; tongue

Instrumentation for monitoring lingual pressure in vibrotactile research - Kingsbury, Gary D; Sansone, E Frank; Kelly, Dan H (Review of Scientific Instruments, 1984)
In order to avoid obtaining variable measurement data it is critical to control pressure applied to the tongue by positioning clamps used in lingual vibrotactile research. A pressure sensing plate, associated electronics, and procedures are described which, when employed with positioning clamps in current use, will permit monitoring lingual pressure during vibrotactile investigations.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/114-981-553-013-894 tex.type: [object Object]
Keywords: dept.cmd

A comparison of the intelligibility of esophageal, electrolaryngeal, and normal speech in quiet and in noise. - Holley, Sandra Cavanaugh; Lerman, Jay W; Randolph, Kenneth (Journal of Communication Disorders, 1983)
The effect of different levels of a multiple-talker background noise on the intelligibility of normal, esophageal, and electrolaryngeal speech was investigated. A superior laryngectomized male speaker and a normal-age matched male speaker produced the speech stimuli used in the study. Audiotape recordings of the speakers were presented to panels of naive listeners. The data from the listeners' responses revealed significant differences in the intelligibility of normal, esophageal, and electrolaryngeal speech as a function of the background noise level. The data did not indicate a superiority of one form of alaryngeal speech over the other in adverse noise conditions. © 1983.
23 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:A1983QY97400007, lens.org/077-212-672-431-70X tex.type: [object Object]
Keywords: Adolescent; Adult; Comparative Study; Female; Human; Male; Noise; Phonetics; Speech Intelligibility; Speech; Alaryngeal; Speech; Esophageal; adolescent; adult; article; comparative study; dept.cmd; esophagus speech; female; human; male; methodology; noise; phonetics; speech intelligibility

Clinical estimation of fundamental frequency: The 3m plastiform magnetic tape viewer - Kelly, Dan H; Sansone, Frank (Journal of Communication Disorders, 1981)
A procedure and method is described to determine the frequency or pitch of tape-recorded voice samples, while keeping the cost of measurement within the reach of practicing clinicians. The method described reduces the uncertainty of pitch determination by comparison techniques and improves the accuracy of clinical estimation of fundamental vocal frequency and pitch. The accuracy, reliability, cost, and ease with which the method can be used makes it a viable tool to be used by the clinician. © 1981.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/065-059-031-584-761 tex.type: [object Object]
Keywords: Human; Methods; Pitch Perception; Tape Recording; Voice Disorders; article; dept.cmd; hearing; human; instrumentation; larynx disorder; tape recorder; technique

Multiplex developmental disorders: the role of communication in the construction of a self - Paul, Rhea; Cohen, Donald J.; Klin, Ami; Volkmar, Fred R. (Child and Adolescent Psychiatric Clinics of North America, 1999)
This article discusses the integration of various aspects of the child's development, particularly the development of language and communication and the way in which these developments interact to enable the child to construct a coherent sense of self. Multiplex developmental disorder is presented as an example of a disorder that affects several of these crucial strands of development. Recent research and controversies regarding the diagnostic descriptions of multiplex and other pervasive developmental disorders are presented. This discussion is used to illustrate the ways in which such disorders affect not only the individual aspects of development, but the child's ability to form a cohesive sense of self. The implications of these difficulties in self-definition for treating children with disorders that affect a variety of aspects of development are also discussed.
8 citations (Crossref) [2023-10-31] Citation Key Alias: pop00136 tex.type: [object Object]
Keywords: *Communication Disorders/di [Diagnosis]; *Developmental Disabilities/di [Diagnosis]; Child; Child Development Disorders; Pervasive/co [Complications]; Child Development Disorders; Pervasive/di [Diagnosis]; Child Development Disorders; Pervasive/px [Psychology]; Child; Preschool; Communication Disorders/et [Etiology]; Communication Disorders/px [Psychology]; Developmental Disabilities/co [Complications]; Developmental Disabilities/px [Psychology]; Humans; Infant; Language Development; affective neurosis; attention deficit disorder; autism; child; cognitive defect; communication disorder; dept.cmd; developmental disorder; disease association; human; mental disease; mental performance; neuropsychiatry; priority journal; review; schizophrenia; social behavior; symptomatology

Communication disorders and children with mental retardation - Cascella, Paul W (Child and Adolescent Psychiatric Clinics of North America, 1999)
This article examines the communication styles of children with mental retardation, emphasizing the assessment and intervention protocols used by health and education professionals. This article highlights the following approaches: a developmental psycholinguistic orientation, a pragmatics approach, and a supportive interdependent format consistent with the 1992 revision of how mental retardation is classified. This article discusses children with mental retardation who show challenging and disruptive behavior.
7 citations (Crossref) [2023-10-31] Place: United States Cascella, P W. Department of Communication Disorders, Southern Connecticut State University, New Haven, USA.
Keywords: *Communication Disorders/co [Complications]; *Intellectual Disability/co [Complications]; Child; Child; Preschool; Communication Disorders/di [Diagnosis]; Communication Disorders/rh [Rehabilitation]; Humans; Infant; Infant; Newborn; Intellectual Disability/rh [Rehabilitation]; Language Tests; Models; Psychological; Psycholinguistics; auditory memory; communication disorder; dept.cmd; interpersonal communication; language; learning; mental deficiency; priority journal; recall; review; social interaction

Assessing communication in children with psychiatric and communication disorders - Kennedy, MD (Child and Adolescent Psychiatric Clinics of North America, 1999)
This article presents issues related to the communication assessment of children with psychiatric and communication disorders. Challenges inherent in assessing this population are discussed. Frequently used assessment instruments and procedures are described. Consideration is given to the assessment of very young or low-functioning children and older or high-functioning children.
0 citations (Crossref) [2023-10-31] Place: United States Kennedy, M D. Department of Communication Disorders, Southern Connecticut State University, New Haven, USA.
Keywords: *Communication Disorders/di [Diagnosis]; *Language Tests; *Mental Disorders/co [Complications]; *Psychometrics/mt [Methods]; Adolescent; Asperger syndrome; Child; Child Development Disorders; Pervasive/co [Complications]; Child Development Disorders; Pervasive/di [Diagnosis]; Child; Preschool; Communication Disorders/co [Complications]; Humans; Male; Mental Disorders/di [Diagnosis]; adolescent; case report; communication disorder; data analysis; dept.cmd; developmental disorder; differential diagnosis; human; intelligence; language ability; male; mental disease; mental task; phonetics; priority journal; problem solving; psychiatric diagnosis; review; school child; speech articulation; speech therapy; standardization; verbal communication

Child and Adolescent Psychiatric Clinics of North America: Preface - Paul, R. (Child and Adolescent Psychiatric Clinics of North America, 1999)
0 citations (Crossref) [2023-10-31]
Keywords: attention deficit disorder; autism; behavior disorder; child psychiatry; cognitive defect; communication disorder; dept.cmd; editorial; mental deficiency; mental disease; priority journal; reading; speech disorder

Discussion: Early speech perception and production - Paul, R. (Journal of Communication Disorders, 1999)
2 citations (Crossref) [2023-10-31]
Keywords: Communication Disorders; Humans; Infant; Infant Behavior; Language Development; Parents; Verbal Behavior; conference paper; dept.cmd; human; infancy; infant; language development; speech development

Assessing speech, language, and communication - Paul, R.; Marans, W.D. (Child and Adolescent Psychiatric Clinics of North America, 1999)
This article discusses the assessment of communication skills in children from birth to 5 years of age. The different methods appropriate for different developmental levels and the relationship of collateral areas, such as hearing, cognition, and speech motor control to the communication process, are addressed. The need for standardized and informal measures is emphasized Case studies are presented to illustrate the principles outlined.
1 citations (Crossref) [2023-10-31]
Keywords: *Language Development Disorders/di [Diagnosis]; *Mental Disorders/co [Complications]; *Speech Disorders/di [Diagnosis]; Child; Preschool; Female; Humans; Infant; Infant; Newborn; Language Development Disorders/pc [Prevention & Control]; Language Development Disorders/px [Psychology]; Language Tests; Male; Mental Disorders/di [Diagnosis]; Nonverbal Communication; Psycholinguistics; Speech Disorders/px [Psychology]; child; child development; dept.cmd; human; infant; intelligence; language disability; medical record; mental disease; priority journal; review; skill; speech articulation; speech disorder; verbal communication

Communication and its disorders - Paul, R.; Rubin, E. (Child and Adolescent Psychiatric Clinics of North America, 1999)
This article defines communication and describes its various disorders. Some of these disorders are associated with other DSM-IV conditions, such as mental retardation or pervasive developmental disorder. Others are specific to the language-learning process. The interactions between communication and psychiatric disorders are discussed. Suggestions for integrating treating approaches among communication disorders and mental health professionals are presented.
1 citations (Crossref) [2023-10-31]
Keywords: *Communication Disorders; Child; Child Abuse; Child Development; Communication Disorders/ep [Epidemiology]; Communication Disorders/et [Etiology]; Communication Disorders/px [Psychology]; Comorbidity; Female; Humans; Infant; Infant; Newborn; Mental Disorders/ep [Epidemiology]; Nervous System Diseases/co [Complications]; Pregnancy; Prenatal Exposure Delayed Effects; Socioeconomic Factors; affective neurosis; autism; brain injury; cerebrovascular accident; child abuse; cocaine; communication disorder; cultural anthropology; dept.cmd; developmental disorder; economic aspect; fetal alcohol syndrome; hearing impairment; interpersonal communication; language disability; mental deficiency; mental disease; mutism; prenatal drug exposure; priority journal; review; social problem; speech disorder; visual impairment

Treatment Efficacy Cognitive-Communicative disorders resulting from traumatic brain injury in adults - Coelho, Carl A; Deruyter, Frank; Stein, Margo (Journal of Speech Language and Hearing Research, 1996)
Traumatic brain injuries (TBI) may result in a broad array of cognitive-communicative impairments. Cognitive-communicative impairments are the result of deficits in linguistic and nonlinguistic cognitive functions. The speech-language pathologist functions as a member of the multidisciplinary team of professionals that collaboratively assess and treat individuals with TBI. The role of the speech-language pathologist includes assessment of all aspects of communication, as well as the communicative implications of cognitive deficits, and swallowing; treatment planning and programming, as determined by the individual's stage of recovery; client and family training/counseling; and interdisciplinary consultation. The effectiveness of speech and language intervention for specific cognitive deficits (e.g., attention, memory, executive functions) as well as general issues of social-skills training and early intervention are illustrated by scientific and clinical evidence from group-treatment and single-subject studies as well as case studies.
46 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/044-522-997-910-510 tex.type: [object Object]
Keywords: *Brain Injuries/co [Complications]; *Cognition Disorders/et [Etiology]; *Cognition Disorders/th [Therapy]; *Communication Disorders/et [Etiology]; *Communication Disorders/th [Therapy]; Activities of Daily Living; Brain Injuries; Brain Injuries/pp [Physiopathology]; Cognition Disorders; Cognitive rehabilitation; Communication Disorders; Communication disorders; Humans; Intervention studies; Speech Therapy; Traumatic brain injury; Treatment Outcome; Treatment outcome; adult; article; attention; brain injury; cognitive defect; communication disorder; consultation; counseling; daily life activity; dept.cmd; female; human; linguistics; major clinical study; male; memory; quality of life; social adaptation; speech therapy; treatment outcome; treatment planning; ⛔ No DOI found

An Investigation of a Method of Simplified Scoring for the Kaufman Hand Movements Test as a Measure of Limb Apraxia: - Neiman, Michael R.; Duffy, Robert J.; Belanger, Steven A.; Coelho, Carl A. (Perceptual and Motor Skills, 1996)
A simplified, 3-category method for scoring the Kaufman Hand Movements test was devised to replace a previously used, more complex 21-category scoring method. The concurrent validity and diagnostic sensitivity of the rescored test as a measure of limb apraxia were investigated in a reanalysis of the test protocols of 23 aphasic adults. Using the Limb Apraxia Test as the criterion measure, a Pearson r of .71 and predictive validity of 100% were obtained. These results encourage further investigation of the Kaufman Hand Movements lest as an efficient measure of limb apraxia.
0 citations (Crossref) [2023-10-31]
Keywords: Adult; Aged; Aphasia; Apraxias; Dominance; Cerebral; Female; Humans; Imitative Behavior; Male; Middle Aged; Motor Skills; Neuropsychological Tests; Observer Variation; Orientation; Psychometrics; adult; aged; aphasia; apraxia; article; dept.cmd; female; hemispheric dominance; human; imitation; male; middle aged; motor performance; neuropsychological test; observer variation; orientation; psychometry; statistics

Impairments of discourse abilities and executive functions in traumatically brain-injured adults. - Coelho, Carl A; Liles, Betty Z; Duffy, Robert J (Brain Injury, 1995)
Preliminary findings from an ongoing investigation of the potential relationship between narrative discourse performance and executive functions in adults with traumatic brain injuries (TBI) are reported. Narrative stories were elicited from 32 adults with TBI. Stories were analysed at three levels: sentence production, intersentential cohesive adequacy, and story episode structure. These measures were then correlated with scores from the Wisconsin Card Sorting Test (WCST), the primary measure of executive function. A significant correlation was noted between a factor score from the WCST and the measure of story structure, but not sentence production or cohesive adequacy. These results suggest that executive functions may be a promising avenue to pursue in the search for underlying causal factors of narrative discourse dysfunction and, therefore to better delineate the nature of communicative deficits secondary to TBI.
93 citations (Crossref) [2023-10-31] Place: England Coelho, C A. Communication Disorders Department, Southern Connecticut State University, New Haven 06515, USA.
Keywords: *Aphasia; Broca/di [Diagnosis]; *Brain Damage; Chronic/di [Diagnosis]; *Brain Injuries/di [Diagnosis]; *Neuropsychological Tests; *Problem Solving; *Speech Production Measurement; Adolescent; Adult; Aphasia; Broca/px [Psychology]; Aphasia; Broca/rh [Rehabilitation]; Brain Damage; Chronic/px [Psychology]; Brain Damage; Chronic/rh [Rehabilitation]; Brain Injuries/px [Psychology]; Brain Injuries/rh [Rehabilitation]; Female; Humans; Male; Middle Aged; adolescent; adult; article; brain injury; clinical article; dept.cmd; female; human; male; speech analysis; speech articulation; speech disorder

Discourse production deficits following traumatic brain injury: A critical review of the recent literature - Coelho, Carl A (Aphasiology, 1995)
This review analyses several recent studies of discourse deficits subsequent to traumatic brain injury. The review describes methodological problems related to incomplete subject descriptions, use of different discourse elicitation tasks and analyses, and examines the findings from each study by level of analysis. The limitations of these findings are discussed and general conclusions regarding discourse abilities following traumatic brain injury are offered. Implications for future research are also presented.
53 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/023-484-036-629-272 tex.type: [object Object]
Keywords: aphasia; brain injury; conversation; dept.cmd; dysarthria; human; injury scale; language disability; peer-reviewed; review

The development of literacy in individuals with severe congenital speech and motor impairments - Foley, B.E. (Topics in Language Disorders, 1993)
39 citations (Crossref) [2023-10-31]
Keywords: dept.cmd

A multicultural annotative bibliography of voice and voice disorders - Dejarnette, Glenda (Howard Journal of Communications, 1992)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/007-333-150-134-195 tex.type: [object Object]
Keywords: African american voice; Asian american voice; Hispanic voice; Multicultural voice; Multicultural voice disorders; Native american voice; dept.cmd

Computer‐assisted tracking simulation (CATS) - Dempsey, James J.; Levitt, Harry; Josephson, Judith; Porrazzo, Josephine (The Journal of the Acoustical Society of America, 1992)
The tracking technique involves a sender reading consecutive segments from a story and a receiver attempting to repeat each segment verbatim. The reliability and validity of the tracking procedure have been criticized based upon uncontrolled variables such as sender, receiver, and text characteristics. To address these problems, a computer-assisted interactive tracking simulation (CATS) system has been developed in which story segments are presented to the receiver via a video laser disc system and repair strategies are implemented through a computer program.
5 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:A1992JG99200008 tex.unique-id: [object Object]
Keywords: dept.cmd